2014
DOI: 10.1007/s11242-014-0390-8
|View full text |Cite
|
Sign up to set email alerts
|

On Water Transfer and Hydraulic Connection Layer During the Convective Drying of Rigid Porous Material

Abstract: The convective drying of a natural porous material, limestone, is investigated in this study, with both experimental and numerical approaches. The first experimental campaign, which focuses on the influence of samples' slenderness, suggests the presence of a hydraulic connection layer between the porous water and the external environment, in spite of the very fine pore structure of the material. This hydraulic transfer enables the fast water evaporation at the beginning of the drying test, when external condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…The basic phenomenological mechanisms of drying in simple systems initially filled with pure liquid have been identified [1][2][3][4][5][6][7]. After a short induction period of variable duration, a Constant drying Rate Period (CRP), associated with a homogeneous desaturation of the medium usually occurs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic phenomenological mechanisms of drying in simple systems initially filled with pure liquid have been identified [1][2][3][4][5][6][7]. After a short induction period of variable duration, a Constant drying Rate Period (CRP), associated with a homogeneous desaturation of the medium usually occurs.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally considered that the onset of this second regime results from a demand of liquid, through the imposed evaporation rate, larger than the liquid flux towards the free surface and resulting from capillary effects. Such a situation would lead the inward growth of a dry region from the sample free surface [1,4,7]. In detail, it was also suggested that two FRP should be considered [4,[17][18][19], associated with the continuous and the discontinuous states of the liquid network.…”
Section: Introductionmentioning
confidence: 99%
“…The drying rate calculated based on equation (2) is filtrated using Lanczos method [13] to reduce noise generated by the subtraction between two mass measurements that only differ from an order of magnitude slightly larger than the weighing measurement error. The obtained curve highlights the two classical distinct drying stages [14,15].…”
Section: Data Treatmentmentioning
confidence: 99%
“…Stage II of drying starts when the internal conductive properties of the soil (permeability, diffusivity) do no longer allow a sufficient water flow to the soil surface to maintain the maximal evaporation rate. Therefore, the transition between the two periods, around the critical water content, expresses the progressive development of an internal mass transfer resistance in series to the previously limiting external mass transfer resistance [13,16]. From the Krischer curves obtained, the maximal drying rates and the critical water contents w crit are deduced.…”
Section: Data Treatmentmentioning
confidence: 99%
“…In the latter case, the most frequently adopted work‐around consists in using a water‐based salt solution, containing elements with high Z , instead of distilled water. For example, concerning visualization of drying in porous media, water‐based solutions of CaI (Shokri et al ., ; Shokri & Sahimi, ) and a suspension of limestone powder in water (Prime et al ., ) have been used. Salt precipitation during drying of porous media has been successfully imaged with XACI for NaCl solutions (Norouzi Rad et al ., ; Norouzi Rad & Shokri, ).…”
Section: Introductionmentioning
confidence: 99%